Complexes of Antimony(III) - Yadav, Ram Nath Prasad (Academic Voices: A Multidisciplinary Journal, 2015)
Lewis acidity of antimony(III) halides and their organo substituted derivatives is well known. The molecules SbX3 are good acceptor and a wide range of neutral complexes have been prepared but it seems antimony trichloride is a weak acceptor as compared to antimony pentachloride. The halide complexes are more interesting because of the part played by the lone pair in determining the stereochemistry where 1:1 complexes have trigonal bipyramidal and 1:2 complexes have square pyramidal configurations. Complexes of antimony trichloride with aromatic hydrocarbon are also known but the presence of organic group in a molecule reduces its capacity to form complexes. DOI: http://dx.doi.org/10.3126/av.v4i0.12357 Academic Voices Vol.4 2014: 45-48